Implementasi Algoritma Genetika pada Tata Ruang Ibukota Kecamatan (Studi Kasus : Desa Hantara) - Dadan Nugraha; Iwan Lesmana; Gian Megantara (Universitas Kuningan, 2021)
Spatial planning is an obligation that must be carried out by each Regional Government. At present, spatial planning is still conventionally planned by the spatial planning company. Regarding with the object of research that the authors examined, namely Hantara Village, Hantara Village did not yet have a plan for how the future projection and development of Hantara Village. With a touch of information technology, for now spatial planning can be done using an application by implementing a method that is Genetic Algorithm into the application .Genetic Algorithm is an optimal search algorithm which is in its implementation the genetic algorithm will look for the most optimal points which is match with the constraints that have been determined based on law 26 of 2007 concerning Spatial Planning. Then the search results of the genetic algorithm data will be visualized by using the features of the mapbox, the online map provider. In software development, the author use the Rational Unified Process (RUP) method which has four stages, namely: Inception, Elaboration, Contruction, and Transition. This application is built use the python programming language, along with html and javascript for visualizing the data. Based on the results of this research the authors can conclude that this research can make a projection of residental area in Hantara village accordance with genetic algorithm and its constraint.Keywords— Sepatial Planning, Genetic Algorithm, Data Visualization, RUP, Python